Participatory redesign of work organisation in hospital nursing: A study of the implementation process. (23rd March 2018) - Stab, Nicole; Hacker, Winfried
Abstract : Aims: The main goal of the study was to apply and analyse a moderated participatory small‐group procedure with registered nurses, which aims at the development and implementation of measures to improve work organisation in hospital wards and nursing units. Background: Participation in job redesign is an essential prerequisite of the successful implementation of improvement measures in nursing. Methods: The study was carried out in a public hospital of maximum care in Germany. We selected 25 wards with the most critical reported exhaustion and general health and applied a series of moderated small‐group sessions in which the registered nurses jointly identified deficits in their work organisation, developed improvement measures, and then implemented and assessed them. Results: Registered nurses of 22 wards actively took part in the small‐group procedure. All nursing units jointly identified organisational deficits, developed possible improvement measures, and implemented them. The nursing teams then evaluated the implemented measures which were already assessable at the end of our research period; nearly all (99.0%) showed improvements, while 69.4% actually attained the desired goals. Conclusion: Participatory small‐group activities may be successfully applied in hospital nursing in order to improve work organisation. Implications for Nursing Management: Participatory assessment and redesign of nurses' work organisation should be integrated into regular team meetings. The nursing management should actively support the implementation process.